Evaluación del ambiente educacional pre-clínico en seis Escuelas de Medicina en Chile - Herrera, Cristian (Scielo, 2015)
The Dundee Ready Education Environment Measure (DREEM) is the most valid and reliable instrument to measure the educational environment (EE) in undergraduate medical education. Aim: To evaluate the EE perceived by undergraduate medical students in Chile, using a Spanish version of the DREEM questionnaire. Material and Methods: The DREEM was applied during 2008 in third, fourth and fifth undergraduate years of six medical schools. The individual results were calculated and means of both global and individual domain scores of the DREEM were compared, by year, gender and between different Schools.Results: One thousand ninety two students (77% of the total universe of students), answered the questionnaire. The mean score of the six Schools was 113.9. The domains of Perception of Learning and Social Self-Perception obtained the lower scores, with a global outcome indicating a more positive than negative EE. Two schools obtained mean scores of 128.32 and 126.87, that were significantly higher than the global scores obtained by other schools. No relevant differences by years or gender were observed. Conclusions: There is a significant variability between the six schools evaluated and two of these obtained significantly better scores than the rest. The identified positive and negative areas will orient the actions to improve the EE for undergraduate medical students